Application of atomic layer deposited dopant sources for ultra‐shallow doping of silicon. Issue 1 (9th December 2013) - Kalkofen, Bodo; Amusan, Akinwumi A.; Lisker, Marco; Burte, Edmund P.; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract The advanced silicon semiconductor technology requires doping methods for production of ultra‐shallow junctions with sufficiently low sheet resistance. Furthermore, advanced 3‐dimensional topologies may require controlled local doping that cannot be achieved by ionimplantation. Here, the application of the atomic layer deposition (ALD) method for pre‐deposition of dopant sources is presented. Antimony oxide and boron oxide were investigated for such application. Ozone‐based ALD was carried out on silicon wafers by using triethylantimony or tris‐(dimethylamido)borane. Very homogeneous Sb2O5 deposition could be achieved on flat silicon wafers and in trench structures. The thermal stability of antimony oxide layers was investigated by rapid thermal annealing experiments. The layers were not stable above 750 °C. Therefore, this material failed to act as dopant source so far. In contrast, ultra‐shallow boron doping of silicon from ALD grown boron oxide films was successful. However, pure B2O3 films were highly unstable after exposure to ambient air. The boron oxide films could be protected by thin Sb2O5 or Al2O3 films that were in‐situ grown by ALD. Low temperature ALD of Al2O3 at 50 °C from trimethylaluminium (TMA) and ozone was investigated in detail with respect of its protective effect on boron oxide. Interestingly, it was observed that already one ALD cycle of TMA and O3 resulted in significant increase in stability of the boron oxide in air. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)